2023
DOI: 10.1038/s41559-023-02257-9
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in noise will affect urban wildlife

Jasmine R. Nelson-Olivieri,
Tamara J. Layden,
Edder Antunez
et al.

Abstract: Understanding how systemic biases in uence local ecological communities is essential for developing just and equitable environmental practices that center both human and wildlife wellbeing. With over 270 million United States residents inhabiting urban areas, understanding the socio-ecological consequences of racially-targeted zoning, such as redlining, will prove critical for urban planning. There is a growing body of literature documenting the relationships between redlining and the inequitable distribution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 107 publications
1
1
0
Order By: Relevance
“…Redlining persisted across the United States from 1933 to 1968 in over 230 cities. , Alongside restrictive deeds, racialized zoning, steering, and social violence, redlining led to land use and decision making that worsened the environmental quality for redlined neighborhoods. ,, In this study, we assessed 868 previously HOLC-graded neighborhoods across eight California cities and found that redlining is strongly associated with environmental quality. Our results enrich the redlining literature by demonstrating that formerly redlined neighborhoods exhibit significantly poorer environmental quality than other HOLC grades, including less investigated hazards such as noise pollution, lead, and contaminated water. This holds implications for human health disparities, as redlined neighborhoods in California are composed of census tracts with higher proportions of Hispanic and Black populations, as well as a people living in poverty, than greenlined neighborhoods . Our results shed light on the enduring, far-reaching impact of redlining, a policy that was abolished almost 60 years ago, on contemporary environmental quality.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Redlining persisted across the United States from 1933 to 1968 in over 230 cities. , Alongside restrictive deeds, racialized zoning, steering, and social violence, redlining led to land use and decision making that worsened the environmental quality for redlined neighborhoods. ,, In this study, we assessed 868 previously HOLC-graded neighborhoods across eight California cities and found that redlining is strongly associated with environmental quality. Our results enrich the redlining literature by demonstrating that formerly redlined neighborhoods exhibit significantly poorer environmental quality than other HOLC grades, including less investigated hazards such as noise pollution, lead, and contaminated water. This holds implications for human health disparities, as redlined neighborhoods in California are composed of census tracts with higher proportions of Hispanic and Black populations, as well as a people living in poverty, than greenlined neighborhoods . Our results shed light on the enduring, far-reaching impact of redlining, a policy that was abolished almost 60 years ago, on contemporary environmental quality.…”
Section: Discussionsupporting
confidence: 63%
“…Our results enrich the redlining literature by demonstrating that formerly redlined neighborhoods exhibit significantly poorer environmental quality than other HOLC grades, including less investigated hazards such as noise pollution, lead, and contaminated water. 33 35 This holds implications for human health disparities, as redlined neighborhoods in California are composed of census tracts with higher proportions of Hispanic and Black populations, as well as a people living in poverty, than greenlined neighborhoods. 36 Our results shed light on the enduring, far-reaching impact of redlining, a policy that was abolished almost 60 years ago, on contemporary environmental quality.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, our results suggest that an individual is more likely to encounter a greater diversity of species with less search effort in California’s greenlined neighborhoods than in nongreenlined neighborhoods. This may potentially be explained by greenlined neighborhoods customarily having increased environmental quality [i.e., higher vegetation cover and reduced ecological disturbances ( 24 , 30 , 45 , 47 )], which in turn improves the likelihood of unique species occupying the given area. This holds broad implications for human well-being in urban spaces, as equity in nature access and quality, as well as promoting positive human-environment relationships (which are more likely with increased access to biodiverse spaces) are increasingly being considered as central issues of environmental justice ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%